Regularity of solutions to a parabolic free boundary problem with variable coefficients. (November 2016) - Backing, Thomas
Abstract: In this work the optimal Lipschitz regularity of viscosity solutions for a type of parabolic free boundary problem with variable coefficients is proved under the main assumption that the free boundary is Lipschitz.